Soft tissue and wound infections due to Enterococcus spp. among hospitalized trauma patients in a developing country - Nonika Rajkumari; Purva Mathur; Mahesh Chandra Misra (Journal of Global Infectious Diseases, 2014)
Soft tissue and wound infections due to Enterococcus spp. are increasing worldwide with current need to understand the epidemiology of the Enterococcal infections of wounds. Hence, we have looked into the distribution of Enterococcus spp. responsible for causing wound and soft tissue infections among trauma patients, its antibiotic resistance pattern and how it affects the length of hospital stay and mortality. A laboratory cum clinical-based study was performed over a period of 3 years at a level I trauma center in New Delhi, India. Patients with Enterococcal wound and soft tissue infections were identified using the hospital data base, their incidence of soft tissue/wound infections calculated, drug resistance pattern and their possible risk factors as well as outcomes analyzed. A total of 86 non-repetitive Enterococcus spp. was isolated of which E. faecium were maximally isolated 48 (56%). High level of resistance was seen to gentamicin HLAR in all the species of Enterococcus causing infections whereas a low level resistance to vancomycin and teicoplanin was observed among the isolates. Longer hospital stay, repeated surgical procedure, prior antibiotic therapy and ICU stay were observed to associate with increased morbidity (P < 0.05) and hence, more chances of infections with VRE among the trauma patients. The overall rate of wound and soft tissue infections with Enterococcus sp. was 8.6 per 1,000 admissions during the study period. Enterococcal wound infection is much prevalent in trauma care facilities especially in the ICUs. Here, a microbiologist can act as a sentinel, help in empirical therapeutic decisions and also in preventing such infections.